8t-10-2t=-6+10+9t

Simple and best practice solution for 8t-10-2t=-6+10+9t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8t-10-2t=-6+10+9t equation:


Simplifying
8t + -10 + -2t = -6 + 10 + 9t

Reorder the terms:
-10 + 8t + -2t = -6 + 10 + 9t

Combine like terms: 8t + -2t = 6t
-10 + 6t = -6 + 10 + 9t

Combine like terms: -6 + 10 = 4
-10 + 6t = 4 + 9t

Solving
-10 + 6t = 4 + 9t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9t' to each side of the equation.
-10 + 6t + -9t = 4 + 9t + -9t

Combine like terms: 6t + -9t = -3t
-10 + -3t = 4 + 9t + -9t

Combine like terms: 9t + -9t = 0
-10 + -3t = 4 + 0
-10 + -3t = 4

Add '10' to each side of the equation.
-10 + 10 + -3t = 4 + 10

Combine like terms: -10 + 10 = 0
0 + -3t = 4 + 10
-3t = 4 + 10

Combine like terms: 4 + 10 = 14
-3t = 14

Divide each side by '-3'.
t = -4.666666667

Simplifying
t = -4.666666667

See similar equations:

| 6y+3x=22 | | x+10(x+1)+5=550 | | 2y+4x=12.50 | | a^2+6a=7 | | -(5-3x)+x=4 | | 2r^3+8r^2+6r=0 | | -3.4x=36 | | x+64=x+59 | | x+64+x+59=75 | | -53=90-11x | | x+64+x+59+75=180 | | 18+6g=2(4c+5) | | 5.9x-1=12.7+6.2 | | -6-3(2k+4)=14 | | 3(a-4)=-21 | | 3y^2+3y-18=0 | | 12r-9=6r+18 | | 15=a+24 | | 7m-17=6 | | -28=p+2 | | 5m-2=2m | | 4x+8=15.4 | | 2x+4+x=3(x-2) | | 4(2x-3)=5x-6 | | 8x+3-4x=5+x | | -5c-12+(-5c)=8 | | 43+8x=187 | | t-9=24 | | 4.7w+11.8(1-w)=10 | | 4(m-2)=-12 | | 88=-11x-44 | | 6x-2y=3x+2y |

Equations solver categories